GIS-based approach for mapping the density and distribution of crossbred cattle - GOPALAKRISHNAN, BOOPATHI; SUGUMARAN, MELKUMARAMANGALAM PALANI; BALAJI, KANNAN; THIRUNAVUKKARASU, MARUTHAMUTHU; DAVAMANI, VEERASWAMY (The Indian Journal of Animal Sciences, 2021)
The current study was carried out to map the crossbred cattle density and distribution in the Thondamuthur block of Coimbatore district in Tamil Nadu. A house to house survey was carried out and information about the number of cattle per farm or household, breed, class, age, etc. were collected. The coordinates of households and farms with cattle were recorded using a GPS device and the locations were used to generate maps in QGIS software. The classes of crossbred cattle found in the study area were Holstein-Friesian crossbred (CBHF), Jersey crossbred (CBJ) and Mixed (Jersey-HF) class (CBJH). In the adult category, CBHF contributed about 28% of the total crossbred population followed by CBJ (20%) and CBJH (14%). In the calves category, including heifers, CBJ was marginally higher at 16% than CBHF (15%) followed by CBJH (7%). The cattle density and distribution were higher in the settlements and sparse in the farms located away from the settlements and least in the areas situated close to the hills. This information can aid in various policy and decision-making process regarding cattle management.